Wydatki na reklamę i reprezentację w świetle ustawy o podatku dochodowym od osób prawnych - Tatarska, Marzena (The Clearing of Marketing Costs in the Light of Law, 2006)
Providing an adequate market position for the companies, which nowadays face fierce competition, requires complex marketing strategies. Past are the times when the costs of presentation, advertising and promoting sales constituted a marginal position in the company's budget. Classifying the advertising costs appropriately is essential for establishing the tax base correctly. This is where the controversies among tax payers and revenue officials arise. On the one hand a taxpayer wants to minimize total costs but on the other hand the lawmakers set limits as far as the advertising costs are concerned. The article presents the most important advertising mechanisms showing the costs of unlimited public and limited private advertising as well as the way how to clear them.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 169-178